The History of Christianity in Rumuolumeni: Origin, Growth, Development, Challenges and Prospects 1912-2024 - Mpigi, Goka M.; Ameme, Onuegbu Isaac (NIU Journal of Humanities, 2025)
This paper is the examination of the history of Christianity in Rumuolumeni kingdom. Rumuolumeni is a community in Obio/Akpor Local Government Area of Rivers State Nigeria. The paper further explores the historical development of Christianity its contribution to the development of the Kingdom.  The introduction of Christianity by European colonizers revolutionized African religious perspectives, influencing indigenous thought patterns and cultural practices. Initially perceived as a tool of colonization, the church's presence facilitated cultural exchange, introduced new ideas, and promoted materialism. Over time, as society evolved, the church experienced dynamic growth, expansion, and increased attendance, transforming the once underdeveloped landscape of Rumuolumeni into a more developed and structured community. This paper examines the historical antecedents of church origin, growth, development, challenges, and prospects in Rumuolumeni, providing insights into the complex interplay between Christianity, culture, and societal transformation. This paper adopts the multidimensional approach drawing insights from the historical and phenomenological methods. The Phenomenological approach gave room for the proper understanding of the phenomena so encountered, and assisted in making a pure objective analysis of data, while the historical approach gave us, the opportunity to give a factual descriptive analysis to data so collected. These methods have been chosen because they help in providing answers to the various questions raised as to why Christian spirituality is holding sway within the existing traditional spirituality. These situations were also studied from available materials and sources of information both formal and informal, Synod reports, conference materials, panel reports and Church bulletins, as well as seminar papers which have been found useful in course of data collection for this work. However, in order to establish as concrete and authentic our findings, interviews were conducted and facts received were used in the work.